Determinants of Interest Rate Pass-Through : Do Macroeconomic Conditions and Financial Market Structure Matter? - Gigineishvili, Nikoloz (IMF Working Papers; Working Paper, 2011)
Numerous empirical studies have found that the strength of the interest rate pass-through varies markedly across countries and markets. The causes of such heterogeneity have attracted considerably less attention so far. Unlike other studies that mainly focus on small groups of mostly developed and emerging markets in the same region, this paper expands the cross-sectional coverage to 70 countries from all regions, including low income, emerging and developed countries. It uses a wide range of macroeconomic and financial market structure variables to uncover structural determinants of pass-through. The paper finds that per capita GDP and inflation have positive effects on pass-through, while market volatility has a negative effect. Among financial market variables exchange rate flexibility, credit quality, overhead costs, and banking competition were found to strengthen pass-through, whereas excess banking liquidity to impede it.